2014
DOI: 10.1016/j.ibmb.2013.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Changes in transcript abundance for cuticular proteins and other genes three hours after a blood meal in Anopheles gambiae

Abstract: Numerous studies have examined changes in transcript levels after Anopheles gambiae takes a blood meal. Marinotti et al. (2006) used microarrays and reported massive changes in transcript levels 3 h after feeding (BF3h) compared to non-blood fed (NBF). We were intrigued by the number of transcripts for structural cuticular proteins (CPs) that showed such major differences in levels and employed paired-end (50 bp) RNA-seq technology to compare whole body transcriptomes from 5-day-old females NBF and BF3h. We de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 35 publications
2
41
0
Order By: Relevance
“…Vannini et al (2014) listed 10 CPs where in situ hybridization had revealed transcripts in the eye. Probes for two, CPR10 and CPR132, had been found exclusively in the eye.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Vannini et al (2014) listed 10 CPs where in situ hybridization had revealed transcripts in the eye. Probes for two, CPR10 and CPR132, had been found exclusively in the eye.…”
Section: Resultsmentioning
confidence: 99%
“…From this we learned that a single structure such as the eyes, legs, or Johnston's organ could be the site of hybridization of numerous mRNAs for cuticular proteins. We have already reported on ten putative CP genes that had transcripts in the developing eye, most associated with cells that form the corneal lens and pseudocone (Vannini et al, 2014). We wondered if these transcripts were actually translated and exported into the cuticle.…”
Section: Introductionmentioning
confidence: 99%
“…gambiae following a blood meal (30). Vannini repeated a similar analysis using Illumina (RNA-Seq), and although our results on non-blood-fed females were similar to the James lab study, we had totally different results with females sampled 3 h after a blood meal (44). Our work was facilitated by collaborating with a former technician of mine, Augustine Dunn, who was then finishing off a bioinformatics degree in James's lab.…”
Section: Wwwannualreviewsorg • Arthropod Proteomics and Genomicsmentioning
confidence: 62%
“…They code for two of the proteins detected in this study and were found in cells beneath the corneal lens (Vannini et al, 2014a). …”
Section: Resultsmentioning
confidence: 87%
“…What was surprising was the large number of proteins we found in the corneal lens, first with in situ hybridization (Vannini et al, 2014a), next with MS/MS (Zhou et al, 2016) and now with EM immunolocalization.…”
Section: Discussionmentioning
confidence: 99%